An Analysis of Asking Opinions in The Textbook and Corpora - Mutiara, Rika (Jurnal KATA, 2019)
The study examined the occurrences of asking opinions in the textbook and the ones in the British National Corpus (BNC). Because the expressions in the textbook occur in isolation, it does not give sufficient context in which the expressions occur. For instance, there are no strategies that the speakers use to make the hearers understand their questions. According to Relevance theory, the speakers tried to give relevant input to the hearers in order to obtain the goal of communication (Wilson & Sperber, 2008). Therefore, the present study analyzed expressions of asking opinions in BNC to provide what strategies the speakers use in order to make the questions relevant for the hearers. A corpus-assisted discourse study was conducted to find the strategies. The strategies were analyzed on the light of Relevance theory. It was found that some expressions were not found in BNC. The speakers applied several strategies namely introducing, asking more questions, giving options, and elaborating.  They provide relevant information when asking questions. When the speakers did not get hearers’ opinions, they tried to give more information or options to elicit hearers’ responses.